2017
DOI: 10.2147/ijn.s142008
|View full text |Cite
|
Sign up to set email alerts
|

Dose and time effect of CdTe quantum dots on antioxidant capacities of the liver and kidneys in mice

Abstract: Although quantum dot (QD)-induced toxicity occurs due to free radicals, generation of oxidative stress mediated by reactive oxygen species (ROS) formation is considered an important mechanism. However, free radical mechanisms are essentially difficult to elucidate at the molecular level because most biologically relevant free radicals are highly reactive and short-lived, making them difficult to directly detect, especially in vivo. Antioxidants play an important role in preventing or, in most cases, limiting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…In the physiological state, ROS are always in a dynamic balance between production and elimination, which is maintained by the antioxidant system in the body. If ROS cannot be removed normally and thus accumulate in the tissues, lipids in cells are oxidized to produce peroxides, which eventually leads to tissue damage and dysfunction [ 35 , 36 ]. MDA can directly reflect the severity of the free radical attack.…”
Section: Discussionmentioning
confidence: 99%
“…In the physiological state, ROS are always in a dynamic balance between production and elimination, which is maintained by the antioxidant system in the body. If ROS cannot be removed normally and thus accumulate in the tissues, lipids in cells are oxidized to produce peroxides, which eventually leads to tissue damage and dysfunction [ 35 , 36 ]. MDA can directly reflect the severity of the free radical attack.…”
Section: Discussionmentioning
confidence: 99%
“…There is also an atypical response of T helper cells (Th) in patients with ulcerative colitis, specifically Th2, which exerts a cytotoxic response against epithelial cells (10)(11)(12). In addition, the recruitment of leukocytes is affected, because UC increases the release of the chemo attractant molecule CXCL8, this activates the leukocytes recruiting from the systemic circulation to the intestinal mucosa, its entrance triggers an inflammatory response with a high production of ROS, which is a defense response to phagocytosis of bacteria, also the granular material or soluble irritating compounds increase ROS levels (13).…”
Section: Denitrase Activity Of Debaryomyces Hansenii Reduces the Oxidmentioning
confidence: 99%
“…The cells overcome the oxidative stress condition mainly by neutralization systems such as superoxide dismutase, catalase and oxide-reductase enzymes that react with ROS and in consequence diminish ROS and RNS (13). The cellular mechanisms to repair oxidative damage are scarce or null, such as the case of protein 3-NT elimination, which has been proposed as irreversible, and although an enzymatic like activity of denitrase for histone 3 to detoxify 3-NT has been demonstrated in humans (20), there are no data that clearly demonstrate the presence of denitrase enzyme in higher eukaryotic organisms.…”
Section: Denitrase Activity Of Debaryomyces Hansenii Reduces the Oxidmentioning
confidence: 99%
“…5 The QDs studied to date are usually quickly taken up by the liver and spleen, and, to a minor degree, by bone. 6,7 It has not been shown that whether the QDs leave these organs once inside or they are ultimately cleared from the organs. Most QDs are made of toxic materials such as cadmium, indium, and arsenide.…”
Section: Introductionmentioning
confidence: 99%